(3SjGSGJ ecGaMI GdabQ (B:s (3OQGSGJ JMdjdjI GdLRGFQ,GdUjf fehPLG (B/s - (3aWjeI, MGLjs ((3YeGf(B: s (3OGQ GdQGjI ddfTQ(B, s, 2017)
(3jVe hGbY GdabQ aj GdLRGFQ,CKQ GdHQGeL GdJfehjI ddaJQI (B2005-2014(3Ydi GdabQ aj GdLRGFQ,JLQHI GdUjf aj ecGaMI GdabQs
(3HHdjhZQGajG(B:(3U(B.181-200s
Keywords: (3GdLRGFQs; (3GdUjfs; (3GdabQs; (3GdeTGcd GdGLJeGYjIs